Sturge-Weber Syndrome: report of a clinical case (Research, Society and Development, 2021)
Sturge-Weber syndrome is a rare congenital developmental pathology that is not hereditary. It is characterized by cerebral cortex angiomatosis, with the presence of cerebral calcifications, epilepsy, facial nevus, and ocular alterations. The present study aimed to perform a case report of Sturge-Weber Syndrome, in a patient seen at the clinic school of the Recife School of Dentistry, presenting intraoral port wine staining, face region, pinna, and cervical region, unilateral location, right side. Because it is a rare syndrome, the present case report incorporated the other cases reported in the literature, providing more knowledge of the dental class about the disease, from the aid to diagnosis to the necessary care in the dental treatment of patients with this syndrome.